UJI ORGANOLEPTIK dan DAYA HAMBAT EKSTRAK ALGA COKLAT (Sargassum Polycystum) TERHADAP JAMUR Candida albicans - Rima Parwati Sari (Fakultas Kedokteran, Universitas Hang Tuah, 2024)
Background: Candida albicans, a fungal normal flora that causes Denture stomatitis. Sargassum polycystum is a brown algae species (Phaeophyceae) which grows almost along the coasts of Indonesia islands, known to have antifungal and antibacterial activities. Purpose: To determine the inhibition of brown algae extract (Sargassum polycystum)’s on the growth of Candida albicans and determine whether Sargassum polycystum extract works as denture cleanser material through organoleptic test. Methods: The sample was Candida albicans equal to 0,5 McFarland (108 CFU/ml). The experiment groups comprises negative control group (K-) with 1% DMSO, positive control group (K+) with 0,2% chlorhexidine gluconate, and treatment groups 1-4 (P1;P2;P3;P4) consecutively with 2,5%; 5%; 10%; 20% Sargassum polycystum ethanol extract macerated for 15 minutes in 5 (Ø 6mm) paper discs. SDA medium was incubated for 24 hours and the visible transparent zone was calculated. Organoleptic test was conducted by asking 10 panelists about the observation on color, smell, and homogeneity level of brown algae extract (Sargassum polycystum) with the concentrations of 2,5%; 5%; 10%; and 20%. The experiment result was analyzed with the Kruskal-Wallis test and the Mann-Whitney test. Results: Experiment material’s inhibitory effect was undetectable as Sargassum polycystum ethanol extract against 1% DMSO solvent’s solubility was not homogeneous. The organoleptic test result showed that color, smell, and homogeneity level of brown algae extract (Sargassum polycystum) was not compliant with antiseptic standards. Conclusion: No inhibitory effect in brown algae extract (Sargassum polycystum) as the organoleptic test proved the antiseptic standards were not fulfilled.